ANALISA PENGARUH BEBAN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN - Ayu Tri Lestari; Hcusna Maharani; Vera Lambort Dhika; Firdaus Arif Raihan; Nisrina Salsabila Zahra (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2024)
This study analyses the influence of workload and work environment on employee performance. Workload includes external aspects such as task and organisation, as well as internal aspects such as stress response. The work environment involves physical and non-physical elements that affect productivity and job satisfaction. The research uses a systematic literature review (SLR) method with article sources from Google Scholar, focusing on the influence of workload and work environment variables on employee performance. The results show that workload management and the creation of a conducive work environment play a significant role in improving employee performance. Therefore, organisations are expected to pay attention to workload balance and create a supportive work environment to optimise employee performance.